2017
DOI: 10.1007/s00380-017-0991-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of echocardiographic parameters to assess right ventricular function in pulmonary hypertension

Abstract: Although measurement of right ventricular ejection fraction (RVEF) may be relevant for evaluation of therapeutic efficacy and/or prognosis in patients with pulmonary hypertension, RVEF obtained by echocardiography has limited accuracy. In contrast, radionuclide and/or magnetic resonance imaging can measure RVEF more reliably. In this study, we investigated the relationship between RVEF measured by radionuclide angiography and the echocardiographic parameters that are recommended by the American Society of Echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Despite the load dependency of RVMPI, the high reproducibility makes it a proper index to estimate RV performance. Furthermore, the acceptable accuracy of RVMPI to assess RV performance was mentioned by other authors in different clinical situations (18)(19)(20). In parallel with other studies, Vizzardi et al (21) documented that pulsed Doppler RVMPI > 0.38 is a predictor of cardiovascular death and hospitalization in HF patients with LVEF < 40% and NYHA class II.…”
Section: Discussionmentioning
confidence: 75%
“…Despite the load dependency of RVMPI, the high reproducibility makes it a proper index to estimate RV performance. Furthermore, the acceptable accuracy of RVMPI to assess RV performance was mentioned by other authors in different clinical situations (18)(19)(20). In parallel with other studies, Vizzardi et al (21) documented that pulsed Doppler RVMPI > 0.38 is a predictor of cardiovascular death and hospitalization in HF patients with LVEF < 40% and NYHA class II.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, both RV-MPI and RVFAC favorably reflected the hemodynamics in patients with CTEPH. Previously, Amano et al reported that RV-MPI is a surrogate marker for the right ventricular ejection fraction (RVEF) assessed by MRI in patients with CTEPH [ 22 ]. RV-MPI is an index that combines RV systolic and diastolic function to evaluate RV function.…”
Section: Discussionmentioning
confidence: 99%
“…16 Other studies have challenged that many of these measurements were not well established prior to their recommendation by the ASE. 20 Finally, sonographers and echocardiographers are often unable to make many of the measurements in clinical practice due to difficult imaging. 21 These measurements have shown varying degrees of correlation with the gold standard of volumetric analysis by cMRI.…”
Section: Introductionmentioning
confidence: 99%